THE OPPORTUNITIES FOR MSMEs IN THE INDUSTRIAL TECHNOLOGY - RZ Abdul Aziz (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Industrials Revolution 4.0 is an opportunity for Indonesia to increase economic growth. Economic growth can be conducted by increasing the number of Micro Small and Medium Enterprises (MSMEs). Moreover, MSMEs is involved by the digital economy through broadband, electronic business (e-commerce), social media, cloud technology, and cellular platforms. Therefore, MSMEs can grow faster and improve, give excellent services and products, and become more innovative and competitive so that productivity also increases. This is able to be an opportunity to change the processes and capture new opportunities in the market. One way to capture these opportunities is to produce good products and give excellence services. The implementation of TQM and quality assurance systems, with Quality Control Circle (QCC) or Quality Control (QC), has a significant impact on the quality of products and services which are produced by MSMEs. TQM will deliver companies to world-class services by providing good products and services so that it can make customers satisfaction. Improving quality and service can be supplemented by improving efficiency and productivity. Furthermore, companies engaged in the business sector have the main orientation on achieving the highest possible profit margins (Profit Oriented). Therefore, the collection of data in the current digital economy is the basis of all businesses in this modern era. These efforts can be done by way of more socializing big data at MSMEs. Finally, technology adoption will improve business performance. MSMEs owners and managers must develop strategies to improve efficiency, reduce costs, and get new customers, build websites, and utilize digital technology to conduct market expansion and increased sales through the Digital Economy Era.Keywords: TQM, QCC, Technology, Digital Economy, Big Data